Is there Market Power in the U.S. Brewing Industry? - Bhuyan, Sanjib (The European Journal of Applied Economics, 2020)
Increased consolidation in the U.S. brewing industry has raised legitimate concern about brewing firms’ ability to exert market power downstream. Using structural models of oligopoly behavior, we estimate market power in the U.S. brewing industry over the 1980-2009 period during which the sector experienced a rapid increase in concentration and the demise of many small firms.  Our results show that the U.S. beer market is price sensitive and both distilled spirits and carbonated soft drinks were substitutes to beer. While we were unable to detect the impact of labor and material costs on the price of beer, we find that Federal tax on beer increased beer price. Our results indicate that while there was some indication of market power, U.S. brewers did not exert oligopoly power over downstream firms (distributors and retailers).